UTILIZATION OF GIS TECHNOLOGY FOR PRIVATE FOREST DEVELOPMENT IN KEDUANG SUB WATERSHED, WONOGIRI DISTRICT - Agus Wuryanta; Beny Harjadi; Budiman Achmad (Agric, 2022)
Private forest development has a strategic objective, namely to supply logs as raw materials for the timber industry. The research was conducted in the Keduang Sub-watershed, Wonogiri District. The research objective was to determine suitable tree species and locations for Private forestdevelopment using a Geographical Information System (GIS). The parameters used were production age, soil texture, elevation, and type of production (wood, Multi-Purpose Tree Species / MPTS). Soil types in the Keduang sub-watershed are Litosol (Entisols), Latosol (Inceptisols), and Mediterranean (Ultisols). To determine suitable tree species and locations for Private forestdevelopment, an overlay (with a GIS tool) is carried out between the soil texture map, elevation map, and land cover/use map. Based on the land cover/use map, the area of land suitable for Private forest development is 4,011.95 ha consisting of scrubs (215.51 ha), fields/moor (3,639.84 ha), rainfed fields (114.68 ha), and pasture (41.92 ha). The results of the contour map analysis show that most of the study area has an altitude of <500 m asl (lowland), which is an area of 24,538.02 ha. The soil texture in the study location was dominated by loam, covering an area of 32,153.85 ha. The results of the plant suitability analysis showed that the study location was suitable for Private forestplants such as Acacia mangium, Azadirachta indica A. Juss, Melia azedarach, Paraserianthes falcataria, A. scholaris, Gmelina arborea, Erythrina variegata, Duabanga moluccana, and Hibiscus macrophyllus. While MPTS plants are Aleurites moluccanus and Ceiba pentandra.